Judgment Bias During Gestation in Domestic Pigs - Bushby, Emily V.; Cotter, Sheena C.; Wilkinson, Anna; Friel, Mary; Collins, Lisa M. (Frontiers in Veterinary Science, 2022)
In humans and rats, changes in affect are known to occur during pregnancy, however it is unknown how gestation may influence mood in other non-human mammals. This study assessed changes in pigs’ judgment bias as a measure of affective state throughout gestation. Pigs were trained to complete a spatial judgement bias task with reference to positive and negative locations. We tested gilts before mating, and during early and late gestation, by assessing their responses to ambiguous probe locations. Pigs responded increasingly negatively to ambiguous probes as gestation progressed and there were consistent inter-individual differences in baseline optimism. This suggests that the pigs’ affective state may be altered during gestation, although as a non-pregnant control group was not tested, an effect of learning cannot be ruled out. These results suggest that judgement bias is altered during gestation in domestic pigs, consequently raising novel welfare considerations for captive multiparous species.